Bullying Victimization and Youth’s Likelihood of Carrying a Handgun - Christensen, James B. (Journal of interpersonal violence, 2025)
Recent research suggests that bullying victimization increases the risk of handgun carrying among adolescents. Yet, little to no research has considered whether different types of bullying victimization (i.e., physical, verbal, cyber) shape handgun-carrying behaviors among youth. Understanding these relationships can, however, inform intervention efforts addressing youths’ access to and motives for carrying handguns. The purposes of this study are twofold. First, we establish whether there is a relationship between bullying victimization and youth handgun carrying. Second, we seek to determine whether certain types of bullying victimization are associated more strongly with handgun carrying than others, using data from the 2022 Florida Youth Substance Abuse Survey (FYSAS, n = 47,572), a statewide representative sample of Florida middle school and high school students. The results from multinomial regression models indicate that physical bullying and cyberbullying victimization were associated with an elevated risk of carrying a handgun in the past 12 months. Interventions that underscore the importance of comprehensive anti-bullying interventions that not only address traditional physical aggression among adolescents but also mitigate the evolving challenges posed by unsupervised digital spaces may reduce the risk of handgun carrying.